Apthous ulcers: Its prevalence and distribution according to gender and site in different age groups-A descriptive study - Amit Kumar; Divya Kashyap (Wolters Kluwer Medknow Publications, 2022)
Objective: Recurrent aphthous ulcer, also known as aphthous stomatitis or canker sores, is the most common idiopathic in nature inflammatory disease of the oral mucosa, causing a great deal of pain and discomfort to the patient. The purpose of this study was to report the prevalence of aphthous ulcers and their distribution according to gender and site in different age groups. Materials and Methods: The present study was conducted over a period of 7 months on patients reporting to the Dental Outpatient Department of GMC, Badaun, who came for a routine dental checkup. A pro forma was created, which contained complete demographic and clinical details of all the patients, namely recorded data for age, gender, and site affected were analyzed using the SPSS program. Results: Out of 7400 patients, 291 were diagnosed with recurrent aphthous ulcers, making its overall prevalence to be 3.93%. Cases were found to be higher in females (50.86%) than in males (49.14%). Maximum cases were reported in the second decade of life (36.77%). The tongue was found to be the most common site affected. Conclusion: The present study has provided relevant information regarding the prevalence and distribution of recurrent aphthous ulcers that will contribute to the better understanding and consequent management of the disease.